Sensitive Thin-Layer Chromatography Detection of Boronic Acids Using Alizarin - Duval, Florine; van Beek, Teris A.; Zuilhof, Han (Synlett, 2012)
A new method for the selective and sensitive detection of boronic acids on thin-layer chromatography plates is described. The plate is briefly dipped in an alizarin solution, allowed to dry in ambient air, and observed under 366 nm light. Alizarin emits a bright yellow fluorescence only in the presence of a boronic acid.
Keywords: boronic acid; TLC; staining reagent; dyes/pigments; fluorescence